Strategi Pengembangan Unit Usaha Bioetanol PT Perkebunan Nusantara XI dengan Pendekatan AâWOT - Wulandari, Kartika; Nurmalina, Rita; Tinaprilla, Netti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2017)
The objectives of this study were (i) to analyze external and internal factors of bioethanol business unit in PT Perkebunan Nusantara XI and (ii) to evolve its development strategy. The study used AWOT analysis, a combination of Analytical Hierarchy Process (AHP) and SWOT analysis. The results of AâWOT analysis are internal factors of company: strengthÂ is availability of raw materials (0.383) and weakness is high production costs (0.536). External factors of company: opportunity is market opportunity (0.340) and threatÂ is the low market index prices (0.305). Strategy prioritized in the development of bioethanol business unit is reducing the cost of production to cut costs that are not important and increasing the efficiency of production facilities in order to gain more profit (0.271).